2012
DOI: 10.1155/2012/237284
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Algal Cells to Engineered Nanoparticles Measured as Algal Cell Population, Chlorophyll a, and Lipid Peroxidation: Effect of Particle Size and Type

Abstract: This paper investigated toxicity of three engineered nanoparticles (ENP), namely, Al2O3, SiO2, and TiO2to the unicellular green algae, exemplified byPseudokirchneriella subcapitatawith an emphasis on particle size. The changes in pH, cell counts, chlorophyll a, and lipid peroxidation were used to measure the responses of the algal species to ENP. The most toxic particle size was TiO2at 42 nm with an EC20 of 5.2 mg/L and Al2O3at 14–18 nm with an EC20 of 5.1 mg/L. SiO2was the least toxic with an EC20 of 318 mg/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 54 publications
4
26
0
Order By: Relevance
“…However, the positive effect was recorded especially for the highest concentrations and the possible explanation (nano-TiO 2 could reduce the competition for nutrients killing the bacteria) proposed by these authors are not applicable to our results, since we have performed the assays under axenic conditions, using the nutrient-rich MBL medium. According to some author's, this stimulation is particularly curious, because the adsorption of NMs to the cells surface and the subsequent block of electrolytes and metabolites transport across the membrane was suggested as the primary mechanism of nano-TiO 2 toxicity to algae (Metzler et al 2012). However, other authors have already reported the stimulatory effects of titanium both in algae and terrestrial plants, in the photosynthetic and enzymes activity, probably caused by the influence of titanium in the uptake of other essential elements by roots (Dumon and Ernst 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, the positive effect was recorded especially for the highest concentrations and the possible explanation (nano-TiO 2 could reduce the competition for nutrients killing the bacteria) proposed by these authors are not applicable to our results, since we have performed the assays under axenic conditions, using the nutrient-rich MBL medium. According to some author's, this stimulation is particularly curious, because the adsorption of NMs to the cells surface and the subsequent block of electrolytes and metabolites transport across the membrane was suggested as the primary mechanism of nano-TiO 2 toxicity to algae (Metzler et al 2012). However, other authors have already reported the stimulatory effects of titanium both in algae and terrestrial plants, in the photosynthetic and enzymes activity, probably caused by the influence of titanium in the uptake of other essential elements by roots (Dumon and Ernst 1988).…”
Section: Discussionmentioning
confidence: 99%
“…EC 50 values were not reported in the study. 63 Metzler et al (2012) 64 65 Figure 2 shows that algae were by far the most sensitive test organisms when compared to bacteria and protozoa. Analogously, in their review on ecotoxicity of synthetic NPs (including ZnO, CuO and TiO 2 ) Kahru and Dubrouguier (2010) 62 showed that algae and crustaceans were the most sensitive and thus probably the 'weakest link' in aquatic exposure to NPs.…”
Section: Toxicity To Alga Pseudokirchneriella Subcapitatamentioning
confidence: 99%
“…Because of being primary agents of organic matter transformation, regeneration of nutrients, and as a food source for higher trophic levels, microorganisms are a great concern for toxicity studies (Foster et al 2011;Pagnout et al 2012). Several studies and reviews have been reported which aimed to determine the toxicity of nano-TiO 2 on different organisms such as microorganisms (Coleman et al 2005;Huang et al 2000;Simon-Deckers et al 2009;von Moos and Slaveykova 2014;Wei et al 1994) and algae (Clément et al 2013;Metzler et al 2011Metzler et al , 2012. However, relatively few studies have dealt with the direct effects of TiO 2 NPs on bacteria.…”
Section: Introductionmentioning
confidence: 99%